Psychometric properties of the Drinking Motives Questionnaire for the Argentinean population - Caneto, Florencia; Cupani, Marcos; Pilatti, Angelina (Revista de Psicología, 2014)
The current study evaluated the psychometric properties -structural validity and internal consistency- of three theoretical models developed to assess drinking motives (Drinking Motives Questionnaire [DMQ], Drinking Motives Questionnaires-Revised [DMQ-R] y Modified Drinking Motives Questionnaires-Revised [M-DMQ-R]) and explored the relationship between different reasons for drinking and the severity of problems arising from alcohol consumption. The sample was composed by 315 youth and young adults from Argentina, aged from 18 to 40, who reported drinking alcohol in the last three months. To evaluate the theoretical models, a confirmatory factor analysis model was employed using maximum likelihood estimation. The results indicated that DMQ and DMQ-R models exhibited excellent and adequate fit indices, respectively. However, the M-DMQ-R model did not show adequate fit to the data. Regarding concurrent validity, enhancement and coping drinking motives, but not social motives, were associated to higher degrees of severity of alcohol problems. Overall, results indicated that DMQ model is a valid and reliable tool to measure drinking motives of youth and young adults from the general Argentinean population.